Methods for Arylethylation of Amines and Heteroarenes - Bracher, Franz (SynOpen, 2018)
Compared with standard N-methylation, benzylation, and alkylation of amines and N-heterocycles, N-arylethylation is significantly more challenging. In this Review the available methods for N-arylethylation are summarized, with a special focus on efficiency, selectivity, availability of the required building blocks, and ecological aspects.
Keywords: arylethylation; phenethylation; alkylation; reductive amination; hydroamination; reduction